Pneumococcal Surface Proteins as Virulence Factors, Immunogens, and Conserved Vaccine Targets - Aceil, Javid; Avci, Fikri Y. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae is an opportunistic pathogen that causes over 1 million deaths annually despite the availability of several multivalent pneumococcal conjugate vaccines (PCVs). Due to the limitations surrounding PCVs along with an evolutionary rise in antibiotic-resistant and unencapsulated strains, conserved immunogenic proteins as vaccine targets continue to be an important field of study for pneumococcal disease prevention. In this review, we provide an overview of multiple classes of conserved surface proteins that have been studied for their contribution to pneumococcal virulence. Furthermore, we discuss the immune responses observed in response to these proteins and their promise as vaccine targets.